Pengaruh Perceived Ease of Use dengan Concern of Information Privacy sebagai Moderator terhadap Intention of Use Mobile Payment di DKI Jakarta - Oktavianus Ardian Hartono (Universitas Tarumanagara, 2022)
The purpose of this research is to identify the effect of Perceived Ease of Use with Concern of Information Privacy as moderating variable towards Intention of Use Mobile Payment in DKI Jakarta. This research is descriptive and verificative. Data from 323 participants were collected through an online questionnaire using Google Form and analyzed by SmartPLS. The results show that Perceived Ease of Use positively affects a user’s Intention of Use and there is no significant relation between Perceived Ease of Use and Intention of Use when moderated by Concern of Information Privacy (CFIP). Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dari Perceived Ease of Use dengan Concern of Information Privacy sebagai moderator terhadap Intention of Use Mobile Payment di DKI Jakarta. Penelitian ini adalah penelitian deskriptif dan verifikatif. Data dari 323 partisipan didapatkan melalui kuesioner daring menggunakan Google Form dan dianalisis menggunakan SmartPLS. Hasil pengujian menunjukkan terdapat pengaruh positif antara Perceived Ease of Use dan Intention of Use dan tidak ada hubungan signifikan antara Perceived Ease of Use dan Intention of Use ketika dimoderasi oleh Concern of Information Privacy (CFIP).